Home-Based Exercise Training for Heart Failure Patients: a Systematic Review - Roby Aji Permana; Wikan Purwihantoro Sudarmaji; Wahyu Sukma Samudera; Agostinha Soares; Yanuar Aga Nugraha (Universitas Airlangga, 2019)
Exercise training is one of the recommendations for a cardiac rehabilitation program to increase exercise capacity and thus quality of life, decreasing both readmission and mortality in terms of heart failure. In spite of the evidence on the benefits and safety of cardiac rehabilitation, the uptake and participation of cardiac rehabilitation by patients with heart failure is currently poor. This study aimed to systematically review the effect of home-based exercise training on heart failure patients. The studies were systematically identified by searching through the chosen electronic databases (Scopus, Science Direct, Proquest, Pubmed, and CINAHL) for articles from the 5 last years. The search algorithm identified a total 164 articles and 15 articles were selected based on the inclusion and exclusion criteria. For the 15 articles, 13 were RCTs, 1 was quasi-experimental and 1 was a retrospective study. The major result of this review shows that home-based exercise has an effect on functional and exercise capacity, quality of life and a decreased rate of readmission within 2-12 months follow up. Home-based exercise has a long-term effect that is more effective than exercise that is hospital-based.